2013
DOI: 10.1371/journal.pone.0063804
|View full text |Cite
|
Sign up to set email alerts
|

Immune Activation in HIV-Infected Aging Women on Antiretrovirals—Implications for Age-Associated Comorbidities: A Cross-Sectional Pilot Study

Abstract: BackgroundPersistent immune activation and microbial translocation associated with HIV infection likely place HIV-infected aging women at high risk of developing chronic age-related diseases. We investigated immune activation and microbial translocation in HIV-infected aging women in the post-menopausal ages.MethodsTwenty-seven post-menopausal women with HIV infection receiving antiretroviral treatment with documented viral suppression and 15 HIV-negative age-matched controls were enrolled. Levels of immune ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 48 publications
(67 reference statements)
6
64
0
Order By: Relevance
“…[22][23][24] Increased immune activation of monocytes was reported to be involved in HIV-1 pathogenesis and thus associated with CVD risk. 17,28,29 In the present study, we demonstrated that in contrast to the decreased percentage of CD14 high CD16 2 monocyte subset, CD14 dim CD16 1 and CD14 high CD16 1 monocyte subsets were expanded during both primary and chronic HIV-1 infection. This was the first report of the monocyte subset distribution in primary HIV-1 infection, and it expanded previous observations that had focused on chronic HIV-1-infected patients, HARRT patients, and elite controllers.…”
Section: Monocyte Subset Frequencies Are Altered During Hiv-1 Infectionsupporting
confidence: 46%
“…[22][23][24] Increased immune activation of monocytes was reported to be involved in HIV-1 pathogenesis and thus associated with CVD risk. 17,28,29 In the present study, we demonstrated that in contrast to the decreased percentage of CD14 high CD16 2 monocyte subset, CD14 dim CD16 1 and CD14 high CD16 1 monocyte subsets were expanded during both primary and chronic HIV-1 infection. This was the first report of the monocyte subset distribution in primary HIV-1 infection, and it expanded previous observations that had focused on chronic HIV-1-infected patients, HARRT patients, and elite controllers.…”
Section: Monocyte Subset Frequencies Are Altered During Hiv-1 Infectionsupporting
confidence: 46%
“…One of these markers, soluble CD25, is a general marker of IA and is elevated in diabetes, autoimmune disease, cancer, and immunodeficiency diseases (46). We previously showed that plasma sCD25 is elevated in HIV + compared with HC postmenopausal women (47). Although sCD25 showed a positive correlation with age in HC, it was selected as a significant negative predictor of vaccine response in the HIV + group only.…”
Section: Figure 4 Coexpression Of Immune Activation Markers On Cd4 +mentioning
confidence: 98%
“…Conceivably, HIVinfected patients may have higher rates and increased risk of CHD because of increased levels of inflammation and immune activation than seronegative patients. This increased immune activation persists even in patients on ART who have achieved virological suppression and immune reconstitution with CD4 cell count >200 mm 3 [33]. Soluble CD163 (sCD163) is a monocyte-macrophage specific scavenger receptor cleaved from activated monocytes and macrophages during inflammation, and elevated levels have been associated with coronary artery disease in the general population and HIV-infected men suggesting this inflammatory and immune pathway may be involved in the pathogenesis of atherosclerosis [34,35].…”
Section: Markers Of Inflammation and Immune Activationmentioning
confidence: 99%